Strategy Alignment as an Effort to Create an Innovation Process to Improve Organizational Performance - Risusantho Te'dang; Suwandi Ng (SIMAK, 2023)
This study aims to investigate the effect of strategy alignment as an effort to create an innovation process to improve organizational performance. The sample used in this study came from the Credit Union Cooperative which is under the auspices of the Indonesian Credit Union Cooperative Center (PUSKOPCUINA) Federation Network. Data was collected using a survey method to the management leaders of the Credit Union Cooperative. By using the path analysis method, the result shows firstly, that strategy alignment has a positive and significant influence on the innovation process. Secondly, strategy alignment has a positive but not significant effect on organizational performance. Thirdly, the innovation process has a positive and significant impact on organizational performance. In addition, by using the Sobel test, the result of the study shows that there is a mediating effect of the innovation process in mediating strategy alignment on organizational performance.